Strengthening BUMDesma Sari Bumi through Subgrade Red Ginger Product Diversification - Santoso, Imam; Miftahurrahmah, Aisyah; Choirun, Annisa’u; Suryadi, Nanang; Wulan, Siti Narsito; Purnomo, Mangku (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Red ginger is a rhizome plant that has the benefit of increasing the body's immune system. BUMDesma Sari Bumi, located in Pule Village, Trenggalek Regency, focuses on processing fresh red ginger into dry simplisia. This is done to extend the shelf life of red ginger. The problem encountered so far is the accumulation of subgrade red ginger in the BUMDesma Sari Bumi warehouse. The solution offered to increase the selling value of subgrade red ginger is to diversify the product into red ginger drink premix powder. The premix powdered beverage product consists of two variants namely red ginger coffee and red ginger chocolate. The approach taken in the empowerment activities of BUMDesma Sari Bumi is Participatory Rural Appraisal which emphasizes direct community involvement as subjects and objects as well as overall activities. Activities carried out include module preparation, training and mentoring on how to make Pemix beverage products, and product manufacturing demonstrations. The resulting assistance activity is a red ginger premix product that has obtained a P-IRT number so that it can increase the selling value of subgrade simplistic.